Experimental and numerical investigation of dissimilar weld characterization in laser welding of duplex 2205 and AISI 1060 steel: Microstructure, mechanical properties and weld geometry - Mohammad Behzad Botlani Esfahani; Arash Karimipour; Mohammad Akbari; Ali Abdollahi; Mohammad Najafi (Heliyon)
Dissimilar laser welding of martensitic AISI 1060 carbon steel and Duplex Stainless Steel 2205 was performed based on an experimental and numerical study. The experiments were then conducted based on central composite design experiments (CCD) and analyzed via the response surface methodology (RSM) by considering the effect of laser welding process parameters (incident laser power, speed of welding, nozzle distance and deviation of laser beam) on the weld joint characterization. The experimental results showed that the laser power had a remarkable effect on the melt pool depth. By increasing the laser power from 250 to 450 W at the focal point position, the melt pool depth was increased from 0.4 to 1.4 mm. The microstructure of the molten pool was mainly composed of the solidification of duplex stainless steel (DSS). The molten pool microstructure included columnar dendritic and inter-dendritic microstructures at the boundary fusion line of the toward duplex 2205 base metal. The cellular microstructure with epitaxial grain growth at the center of the molten pool was then formed. According to the numerical simulation results, by increasing the laser power from 250 to 400 W, the extension of high temperature region (more than 1800 °C) was raised to about 150 percent at both depth and width. According to the tensile tests results, the joint fracture surface of the carbon steel side of the joint showed a brittle fracture mechanism due to the martensitic nature of the microstructure of carbon steel, while the fracture cross-section of the DSS side of the joint had a mostly ductile fracture mode, as compared to carbon steel. By increasing the laser beam energy density to more than 0.05 MW/cm2, a coarse grain cellular dendrite was formed at the fusion zone toward AISI 1060 steel along with tempered martensitic microstructure at the heat affected zone of the AISI1060 base metal. This led to the transformation of the joint fracture mechanism from a brittle one to a ductile one. The maximum tensile stress of the dissimilar joints was lower than that of both base metals, although the maximum tensile strength of 550 MPa was obtained at the focal point position and the laser power of 450 W. By increasing the laser power from 400 to 450 W, the microhardness at the region near the fusion line of the duplex stainless steel was increased by about 50 HV, while at the center of the fusion zone, the maximum increase rate reached to 250 HV.